2016
DOI: 10.1121/1.4962343
|View full text |Cite
|
Sign up to set email alerts
|

Coastal sound-field change due to typhoon-induced sediment warming

Abstract: Typhoon induced sediment warming has been proven important to coastal sound-field change in this study. It was observed that the temperature of the bottom waters off the coast of Qingdao increased by 5 °C after the passage of typhoon Damrey in 2012. Sediment warming due to bottom-water temperature increase was calculated and the change in sediment sound speed was estimated. Transmission loss (TL) was simulated both with and without consideration of the change in sediment sound speed induced by temperature vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Shi et al [26] attributed the unusual cooling in the northwestern SCS after the passage of Typhoon 'Mujigae' in the autumn of 2015 to the intrusion of the cold air jet from the Tibetan Plateau. Furthermore, several studies have indicated that the impact of TCs in shallow water can reach the bottom of the sea [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [26] attributed the unusual cooling in the northwestern SCS after the passage of Typhoon 'Mujigae' in the autumn of 2015 to the intrusion of the cold air jet from the Tibetan Plateau. Furthermore, several studies have indicated that the impact of TCs in shallow water can reach the bottom of the sea [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…For the water column, BHF integrated over half a year can warm or cool the bottom 10 m of the water column by more than 18C [estimated using DT 5 ( BHFdt)/(rC 3 10)]. For sediment, BHF driven by synoptic and seasonal bottom water temperature variations can significantly change the sediment temperature profile, which then has a significant effect on the sediment sound-speed profile and thus the shallow sea acoustic field and seismic wave propagation (Day 2016;Yang et al 2016). In addition, the sediment temperature has an important effect on the benthic fluxes of nitrogen, carbon, and many other biogeochemical processes (Kristensen et al 1992;Hancke et al 2014;Crespo et al 2017;Griffiths et al 2017;Meng et al 2022).…”
Section: Introductionmentioning
confidence: 99%